2021
DOI: 10.3389/fimmu.2021.621532
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Dysbiosis and Autoimmune Pancreatitis

Abstract: Autoimmune pancreatitis (AIP) is a chronic fibro-inflammatory disorder of the pancreas. Recent clinicopathological analysis revealed that most cases of AIP are pancreatic manifestations of systemic IgG4-related disease (IgG4-RD), a newly established disease characterized by enhanced IgG4 antibody responses and the involvement of multiple organs. Although the immuno-pathogenesis of AIP and IgG4-RD has been poorly defined, we recently showed that activation of plasmacytoid dendritic cells (pDCs) with the ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Nakano and Takano reported two cases with negative serum and histological IgG4 levels, 6,7 and Hart et al also reported similar cases 8 . The pathogenic function of IgG4 in AIP is still unknown, and studies suggest that IgG4 antibodies have weak complement system activation and FC‐γ binding ability, and their elevated levels may be a result of chronic inflammation 9,10 . Low serum IgG4 levels may also be due to false‐negative results caused by the prozone phenomenon 11 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nakano and Takano reported two cases with negative serum and histological IgG4 levels, 6,7 and Hart et al also reported similar cases 8 . The pathogenic function of IgG4 in AIP is still unknown, and studies suggest that IgG4 antibodies have weak complement system activation and FC‐γ binding ability, and their elevated levels may be a result of chronic inflammation 9,10 . Low serum IgG4 levels may also be due to false‐negative results caused by the prozone phenomenon 11 .…”
Section: Discussionmentioning
confidence: 96%
“…8 The pathogenic function of IgG4 in AIP is still unknown, and studies suggest that IgG4 antibodies have weak complement system activation and FCγ binding ability, and their elevated levels may be a result of chronic inflammation. 9,10 Low serum IgG4 levels may also be due to falsenegative results caused by the prozone phenomenon. 11 Histological negativity for IgG4 is closely related to the extent of fibrosis, and severe fibrosis can hinder immune cell infiltration, especially in RPF, 12 which is consistent with the results of histological IgG4−/+ staining in our three cases (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…There have been related alterations in microbiota with autoimmune pancreatitis in experimental models, suggesting that indeed dysbiosis is responsible, at least in part, for inflammatory processes such as pancreatitis [ 80 ]. However, not only in pancreatitis but changes in the microbiome have been associated with different diseases such as type 1 diabetes and even pancreatic cancer [ 81 ].…”
Section: Gut Microbiota Shapes Pancreatic Beta-cellsmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that microbiota dysbiosis is the critical factor for engendering autoimmune diseases [ 77 ]. For instance, the in vivo results showed that intestinal microbial imbalance promoted the initiation of autoimmune pancreatitis by enhancing the production of IFN-α and IL-33 released by plasmacytoid dendritic cells [ 78 ]. In addition, intestinal microbiota dysbiosis caused by constipation increased the number of Th17 cells and Teff17 cells in the brain and spinal cord as well as promoted the secretion of cytokines in serum, which deteriorated experimental autoimmune encephalomyelitis in mice [ 79 ].…”
Section: Introductionmentioning
confidence: 99%